The DNA damage response: Balancing the scale between cancer and ageing - Seviour, Elena G. (Impact Journals LLC, 2010)
Defects in the DNA damage response often lead to an increased susceptibility to cancer, and so the DDR presents an interesting set of novel therapeutic targets. The maintenance of genomic integrity by the DDR has also been found to be involved in the process of organismal ageing. While the removal of cells containing damaged DNA can be beneficial in the prevention of cancer, it may contribute to both normal and pathological ageing.